Beverage quality of most cultivated Coffea canephora clones in the Western Amazon - Dalazen, Janderson Rodrigues; Rocha, Rodrigo Barros; Pereira, Lucas Louzada; Espindula, Marcelo Curitiba; Alves, Enrique Anastacio; Souza, Carolina Augusto de (Coffee Science - ISSN 1984-3909, 2020)
Most of the Western Amazon coffee production is made from growing unregistered clones, selected by the coffee growers themselves. The aim of this study is to evaluate the sensory profile and genetic diversity of the most cultivated Coffea canephora clones in the Western Amazon. Coffee samples at cherry stage of the clones 03, 05, 08, 25 and 66 were collected at eight municipalities in the main coffee growing zones, with altitudes ranging from 86 to 381 meters. Beverage quality was evaluated according to the Robusta Cupping Protocols and estimates of the genotype × environment interaction (GE) were made interpreting non-parametric and multivariate methods. The GE interaction was significant and the genetic component was also important to the expression of beverage quality (h2=82,23). The clones 25 and 05 have good attributes and mean score near 80 points. Sweetness was the sensory descriptor with the greatest impact on beverage quality of these two clones. Harshness was the descriptor that had the greatest negative impact on beverage quality of clone 66. The clones had complexities that differed and that were not necessarily associated with greater beverage quality. Despite the differences in their beverage attributes, these clones that are grown for their high productivity presented low genetic diversity of the beverage quality. Key words: Fine robusta coffee; sensory analysis; genetic parameters.